Eco-friendly cubic-ZnS coupled Cu7S4 spines on chitosan matrix: Unravelling defect-engineered nanoplatform for the photodegradation of p-chlorophenol. (15th January 2023) - Janani, B.; Balakrishnaraja, R.; Elgorban, Abdalla M.; Bahkali, Ali H.; Varma, Rajender S.; Syed, Asad; Khan, S. Sudheer
Abstract: Novel ZnS–Cu7 S4 nanohybrid supported on chitosan matrix, as an ideal photocatalyst, was fabricated by the sonochemical method wherein high-resolution transmission electron microscopy (HRTEM) and X-ray powder diffraction (XRD) analysis confirmed the co-existence of both ZnS and Cu7 S4 ; presence of vacancy sites in ZnS was verified by electron paramagnetic resonance (EPR) analysis and their introduction could promote two-photon excitation facilitated visible light response and charge transport/separation. The type II interface is formed in the ZnS–Cu7 S4 /Chitosan heterojunction owing to interstitial states that promote charge separation. The ZnS–Cu7 S4 /Chitosan was used for the photodegradation of a pharmaceutical pollutant, p -chlorophenol (PCP); over 98.8% of PCP photodegradation was achieved under visible-light irradiation where the ensued ·O2 − and ·OH serve a key role in the photodegradation of PCP. In vitro cytotoxicity studies substantiated that the ZnS–Cu7 S4 /Chitosan is nontoxic to the ecosystem and human beings and endowed with promising photodegradation properties and accessibility via an environmentally friendly design, bodes well for its potential remediation applications. Graphical abstract: Image 1 Highlights: ZnS–Cu7 S4 /chitosan type II heterojunction showed 98.8% photodegradaion of p-chlorophenol. Defect engineering to promote synergistic charge separation and visible-light absorption. The Cu7 S4 and ZnS NPs appears to be in spine and nanocube shaped. Formation of both ·O2 − and ·OH radicals to boost pollutants degradation. The In vitro cytotoxicity assay suggests that ZnS–Cu7 S4 /chitosan is non-toxic.